Kompetensi, Komitmen, dan Intrapreneurship Pustakawan dalam Mengelola Perpustakaan di Indonesia - Endang Ernawati (Perpustakaan IPB, 2005)
The paper explores how competence and commitment affect librarians in achieving their better performance. Both competence and commitment can be gained through internal and external struggles. Internal struggle means that the librarian have to develop their characters into the targetsthat have been set for their performance indicator. Internal struggle starts when the librarians try to know their identities, by analysing their physical’s strengths and weaknesses, knowing their attitudes, personalities, and talents until they find their self-concept. This self- concept can be continued into the stage of finding personality or themselves, in the sense that they can recognize their self confidence as well as values. This condition becomes a basic for their self-development inwhich they are able to achive their personal identity and become a self-confident persons or independent persons. They become “good” librarians who are easily to be motivated, creative, and innovative to meet their users’ needs. External struggle comes from library environment where theywork, including giving services to users. How “smart” they are in developing databases, preparing book access, giving retrieval guidance to users are practices that are able to improve their smartness.Sets of managerial tools related to librarians’ performance can also develop librarians’ competence and commitments. Starting from Balanced Scorecards that can be adopted into several versions in relation to the actual library operation, competences and commitment assessment in the form of performance indicator are available for every librarian including libray staff. Intrapreneurship is attitudes that can be developed by librarians who possess competence and commitment, especially to face their changing environment from tradional into digital operations. Hopefully, by having competence, commitment, and intrapreneurship, librarians become independent persons so that they are capable to maintain digital library operation and management.